The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.3400/avd.cr.15-00103
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Disseminated Intravascular Coagulation after Thoracic Endovascular Aortic Repair

Abstract: I report a hemorrhagic complication due to disseminated intravascular coagulation after thoracic endovascular aortic repair for a dissecting aortic aneurysm. A 74-year-old man underwent thoracic endovascular aortic repair and carotidcarotid artery bypass to close the primary entry site of the dissecting aortic aneurysm. Postoperatively, he developed a gradually expanding cervical hematoma. Laboratory data showed disseminated intravascular coagulation. He could not extubated until postoperative day 6 because of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…The exact mechanism in this regard has not been elucidated. Most researchers consider that DIC after TEVAR of aortic dissection is secondary to consumptive coagulopathy caused by persistent retrograde flow in the false lumen [ 11 , 12 ]. Identification and preventative substitution therapy for patients at high risk may help to prevent DIC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The exact mechanism in this regard has not been elucidated. Most researchers consider that DIC after TEVAR of aortic dissection is secondary to consumptive coagulopathy caused by persistent retrograde flow in the false lumen [ 11 , 12 ]. Identification and preventative substitution therapy for patients at high risk may help to prevent DIC.…”
Section: Discussionmentioning
confidence: 99%
“…Open surgery may be a radical treatment to correct the hemorrhagic diathesis but is quite invasive [ 13 ]. With rapid advances in endovascular technology, different methods for sealing re-entry tears have emerged [ 2 , 4 , 7 , 12 ]. However, surgical or endovascular intervention may not be suitable for all patients, especially those with high operative risk.…”
Section: Discussionmentioning
confidence: 99%
“…Kotani et al reported a case of worsened coagulopathy resulting in a gradually expanding cervical hematoma after TEVAR for primary entry closure of chronic type B dissection. 3) The authors speculated that DIC might occur secondary to thrombus formation in the false lumen after TEVAR. Sasaki et al reported that prothrombin time, platelet count, and fibrinogen levels tended to be normalized by the 7th postoperative day.…”
Section: Discussionmentioning
confidence: 99%
“…Her blood test results gradually and slightly worsened temporarily, probably due to thrombosis in the false lumen. Her platelet count decreased from 3.9 × 10 4 to 2.2 × 10 4 /mm 3 and her fibrinogen level decreased from 1460 mg/L to 830 mg/L. These values gradually recovered 10 days after abdominal cavity the next day.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation